Mamma, mamma, barn - En rättshistorisk analys av samkönade par och föräldraskap i Sverige - Ståhlgren,Ebba (2024)
Since 2003, same-sex couples in Sweden have been able to be considered as adoptive parents and thus become legal parents. This was, however, controversial and many of the consultation bodies and speakers in the Riksdag were critical of the proposal. They emphasized that too little research had been presented, that children need a mother and a father, and that different-sex couples might find it more difficult to adopt as other countries would view the decision with disapproval. In 2005, same-sex couples were given access to statefunded assisted reproduction. The consultation bodies and members of the Riksdag were divided on this issue. Approximately half supported the proposal, while others criticized, among other things, that it could be burdensome for children to grow up in a different family structure, that it could extend waiting times for different-sex couples, and that the issue had not been sufficiently investigated. It took until 2022 before a presumption of parenthood was introduced. This time, most of the consultation bodies and members of the Riksdag approved, with arguments concerning the positive aspect that more children could have two legal parents when they are born. However, criticism was expressed against the annulment rules, which were considered too extensive. Using a legal historical method and a norm-critical perspective, the essay examines the Swedish legal development regarding same-sex couples and parenthood. This includes looking at central interests and reoccurring arguments. The analysis discusses these aspects in relation to the changes described above. The conclusions drawn are that the legal development regarding same-sex couples' parenthood took place gradually over the years. The development became less controversial over time and the direction increasingly pointed towards gender neutrality in the legislation. Central interests were the best interests of the child, norms and criticism of the regulatory system. Recurring arguments concerned the research basis, the best interests of the child and what types of family constellations that society should encourage.
Keywords: rättshistoria; familjerätt